MAVZU: MA’LUMOTLARNI KORRELYATSION TAHLIL QILISHDA MINITAB DASTURIDAN FOYDALANISH - Isroilbek Ergashev Abdirashid o‘g‘li (Galaxy International Interdisciplinary Research Journal, 2022)
This article describes the use of MINITAB, one of the modern computer programs, in the statistical analysis of data, as well as the simplification of the process of statistical analysis of data and the drawing of appropriate conclusions.